FITOFARMAKA SOLUSI MENGATASI PERMASALAHAN PENYAKIT IKAN YANG RAMAH LINGKUNGAN : SEBUAH TINJAUAN - Rimalia, Anny (Fakultas Pertanian UVAYA Banjarmasin, 2024)
Phytopharmaceuticals are currently the focus for overcoming fish disease problems which cause environmentally friendly aspects. Phytopharmaceuticals are the preparation and use of medicinal plants in the fisheries sector as a preventive measure and treatment of disease. Efforts to control fish diseases in various ways include phytomarfaca, environmentally friendly, safe for cultivated biota and consumers (food safety). Phytopharmaceuticals as growth promoters, antibacterial agents, anti-fungal agents, anti-parasitic agents, antioxidant agents, immunostimulants for fish, adjuvants in vaccines, antiviral agents. Phytopharmaceuticals are applied according to the age or size of the fish, the method of feeding and the length of time it is administered. The length of time for oral administration is not always the same depending on the type of herbal given